KAJIAN EKSPLORATIF AGIHAN HUJAN JAM-JAMAN DI PULAU JAWA - , ERIK LAUW ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Management of water resources has many problems such as data were not complete, the analysis was not describing the real condition of region and also the rainfall stations were not spread evenly. This research aimed to get formulation of rainfall distribution was can be applicated with the hydrological condition in Island of Java. Central Java is one of regions in Indonesia were has complete rainfall data, it can be support to reach the aims of this research. There are many formulations of rainfall distribution that can be used to transform the daily rainfall. The equations were used in a lot of cases showed significant deviation. It is form of better rainfall distribution study according to watershed condition. The rainfall duration analysis is carried out by using automatic rainfall recoder data collected in Central Java. All rainfall data that grater 50 mm/ day were selected for analysis. These data are divided into 4 groups i.e. 50 mm â¤ P < 75 mm, 75 mm â¤ P < 100 mm, Pâ¥100 mm, and Pâ¥50 mm. For each groups the analysis consist of two many aspect, its rainfall duration and rainfall pattern. Average rainfall duration for each contents is calculated by using geometric average for all rainfall data. The average rainfall pattern is obtained by averaging all the rainfall pattern. The results shown that rainfall distribution at 6 watersheds located in Central Java has similar pattern. Those rainfall distribution almost coincide with each other, so it can be represented by a single rainfall distribution pattern, called Central Java pattern.The pattern with 5 hour rainfall duration is 28%, 57%, 79%, 92%, and 100%.